Unplugged play. Toddler : 155 activities & games for ages 1-2 - Conner, Bobbi (Workman Publishing, 2020)
"From Tunnel Tube to Party Play Dough, Bumper Ball to Hoop-Dee-Do, here are more then 150 screen-free games and activities to help kids enjoy the wholesome, old-fashioned experience of playing creatively and freely ... without technology. There are outdoor games and indoor games, games to play solo and games to play with others, crafts, songs, guessing games, puppet ideas, playdate and party favorites -- even instant activities to do at the kitchen table while dinner's cooking. All games are toddler-tested and approved!" --